2001
DOI: 10.1080/mmy.39.5.423.428
|View full text |Cite
|
Sign up to set email alerts
|

Levels of specific antigen (gp43), specific antibodies, and antigen-antibody complexes in saliva and serum of paracoccidioidomycosis patients

Abstract: The present study analyses human immunoglobulin G (IgG) antibodies directed against the Paracoccidioides brasiliensis exoantigen, gp43, as well as the presence of gp43-IgG immune complexes (ICs) in 31 samples of saliva and serum from 19 patients with paracoccidioidomycosis (PCM) and 12 normal donors. Additional analysis of secretory IgA (sIgA) was performed on the same saliva samples. Consistent with previous findings, a significant increased specific IgG level was observed in PCM patients' saliva and serum (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…It is very well known that chronic inflammation of the mucosa stimulates production of IgA antibodies 1 9 10 . In addition, the secretory IgA in saliva from PCM patients may be indicative that it has a protective role regarding antigen neutralization on mucosal surfaces 15 . Previous studies showed that IgG1 antibodies were present, frequently at high levels, in subacute and chronic PCM patients 1 11 .…”
Section: Discussionmentioning
confidence: 99%
“…It is very well known that chronic inflammation of the mucosa stimulates production of IgA antibodies 1 9 10 . In addition, the secretory IgA in saliva from PCM patients may be indicative that it has a protective role regarding antigen neutralization on mucosal surfaces 15 . Previous studies showed that IgG1 antibodies were present, frequently at high levels, in subacute and chronic PCM patients 1 11 .…”
Section: Discussionmentioning
confidence: 99%
“…The gp43 glycoprotein, one of the most important immunodominant antigens of P. brasiliensis, has been extensively investigated, particularly in relation to diagnosis [20][21][22] . Gp43 has been detected at higher levels in PCM patient sera as circulating antigens 22 and in CSF and bronchoalveolar lavage (BAL) fluid samples from PCM patients 11 .…”
Section: Discussionmentioning
confidence: 99%
“…The gp43 glycoprotein, one of the most important immunodominant antigens of P. brasiliensis, has been extensively investigated, particularly in relation to diagnosis [20][21][22] . Gp43 has been detected at higher levels in PCM patient sera as circulating antigens 22 and in CSF and bronchoalveolar lavage (BAL) fluid samples from PCM patients 11 . However, recently the existence of a P. brasiliensis isolate presenting differences in this major antigen coding gene gp43 23,24 has been demonstrated and speculation of the possibility of a new species in the genus Paracoccidioides has been noted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations